Penyuluhan Hukum Tentang Upaya Penyelesaian Sengketa Hak Milik Atas Tanah - Jenny Kristiana Matuankotta; Mahrita Aprilya Lakburlawal (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The general public's lack of knowledge about the importance of land registration, as well as land registration procedures, especially land ownership rights, causes conflicts between residents in the community. When a dispute occurs, the community's lack of understanding of the dispute resolution procedure, either through litigation or non-litigation, causes the community to tend to be reluctant to fight for their land rights.Purposes of Devotion: To provide knowledge about Efforts to resolve disputes over land ownership rights that can be pursued through litigation or judicial institutions or non-litigation channels along with their advantages and disadvantages, with the hope that people who are in dispute regarding land ownership rights can take the right path. in an attempt to resolve it. Method of Devotion: Legal counseling is carried out using a panel discussion method where the presenters first present the material in turns, followed by a questions and answers session between the community and the presenters.Results of the Devotion: Ward Benteng especially in RT 002/RW 006 is one of the areas in Ambon City which is quite dense so there tends to be a dispute over land ownership rights among its citizens, especially related to the typology of disputes, namely control without rights where there are residents who occupy land belonging to them. other residents with the permission of the owner who then secretly took care of the registration of the land without the owner knowing, while the owner himself had not yet registered the ownership of the right due to lack of knowledge about land registration, the community's lack of understanding of legal remedies that can be taken when a land dispute occurs causes landowners to lose their rights to land.